2020
DOI: 10.3390/nano10102055
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Characteristics from Homogeneous Resistive Switching in Pt/Al2O3/TiN Stack

Abstract: In this work, we propose three types of resistive switching behaviors by controlling operation conditions. We confirmed well-known filamentary switching in Al2O3-based resistive switching memory using the conventional device working operation with a forming process. Here, filamentary switching can be classified into two types depending on the compliance current. On top of that, the homogeneous switching is obtained by using a negative differential resistance effect before the forming or setting process in a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 52 publications
4
28
0
Order By: Relevance
“…They observed that applying appropriate stop voltage sweep prior to the LRS, at the negative differential region (NDR) voltage regime, can induce homogeneous switching in the Pt/Al 2 O 3 /TiN devices. Even though the I -V hysteresis of homogeneous switching is less obvious than the filamentary, it was reported that the synaptic behavior of the homogeneous switching is significantly improved, confirming the analog nature of the device [15]. A similar result was also observed in Pt/WO x /W device [16].…”
Section: Filamentary To Homogeneous Switching Transformationsupporting
confidence: 59%
See 2 more Smart Citations
“…They observed that applying appropriate stop voltage sweep prior to the LRS, at the negative differential region (NDR) voltage regime, can induce homogeneous switching in the Pt/Al 2 O 3 /TiN devices. Even though the I -V hysteresis of homogeneous switching is less obvious than the filamentary, it was reported that the synaptic behavior of the homogeneous switching is significantly improved, confirming the analog nature of the device [15]. A similar result was also observed in Pt/WO x /W device [16].…”
Section: Filamentary To Homogeneous Switching Transformationsupporting
confidence: 59%
“…The reversed bias made the switching layer consists of two regions, the oxygenrich region (below the top electrode) and the oxygen-deficient region (above the electrode), which transformed the filamentary into homogeneous switching. The reversed-biased technique can also be useful to transform filamentary bipolar to homogeneous bipolar, as reported by Ryu H. and Kim S. shown in Figure 3(b) [15]. They observed that applying appropriate stop voltage sweep prior to the LRS, at the negative differential region (NDR) voltage regime, can induce homogeneous switching in the Pt/Al 2 O 3 /TiN devices.…”
Section: Filamentary To Homogeneous Switching Transformationmentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, there have been many efforts to use RRAM as a synapse device for hardware neuromorphic systems [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Multiple conductance can be achieved by using gradual set and reset switching behaviors and low-power operation is one of the strong points of RRAM.…”
Section: Introductionmentioning
confidence: 99%
“…The reset process occurs by Joule heating and it is accompanied by high current. Representatively, unipolar resistive switching has been reported a great deal in NiO, TiO 2 , ZnO, ZrO 2 , and HfO 2 [18][19][20][21][22][23][24][25][26][27]. Although research on URS has been conducted for a long time, the poor distribution of high current, voltage, and resistance values have not been resolved.…”
Section: Introductionmentioning
confidence: 99%